Lightweight long-life asphalt pavement composite layer and construction method of pavement structure

By using a combination of high toughness, anti-slip ultra-thin wearing layer, anti-rutting composite modified mid-surface layer, high toughness porous anti-fatigue leveling layer and high-viscosity asphalt synchronous gravel seal layer in the asphalt pavement structure, the problem of traditional asphalt pavement is solved. The problems of large structural thickness, high resource consumption and poor durability have led to the realization of lightweight, long-life and high-performance asphalt pavement structures.

CN119352350APending Publication Date: 2025-01-24CENT FORTUNE CREATION TECH GRP CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411561172.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Traditional asphalt pavement structures have problems such as large thickness, high resource consumption and poor durability, especially technical problems such as reflective cracking and fast anti-slip attenuation.

Method used

The construction method of a composite layer of asphalt pavement on the lightweight long life is adopted, from top to bottom in order to be high -tough anti -slip ultra -thin wear layer, compound modified midfield layer, high tough porous anti -fatigue flat layer and high sticky layer and high stickiness The asphalt synchronous gravel seal layer, by improving the performance of asphalt and feeding, compounding of special materials, optimization of mixed materials, and improvement of pavement structure combinations, improve the anti -fatigue capabilities, low -temperature crack resistance, high temperature stability, etc. of the overall asphalt structure layer, etc. Comprehensive road performance.

Benefits of technology

While the overall thickness of the semi -rigid grass -roots asphalt pavement is realized, its durability and quality of use are improved, and resources can be saved and extended the service life of the pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352350A_ABST
    Figure CN119352350A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of road engineering, and discloses a light-weight long-service-life asphalt pavement composite layer and a construction method of a pavement structure, and the light-weight long-service-life asphalt pavement composite layer sequentially comprises a high-toughness anti-skid ultrathin wearing layer, an anti-rutting composite modified middle surface layer, a high-toughness porous anti-fatigue leveling layer and a high-viscosity asphalt synchronous gravel sealing layer from top to bottom; the thickness of the high-toughness anti-skid ultrathin wearing layer is 1.5-3.0 cm, and the structural depth of the surface of the high-toughness anti-skid ultrathin wearing layer is not less than 0.8 mm; the thickness of the anti-rutting composite modified middle surface layer is 2.5 to 4.5 cm; the thickness of the high-toughness porous anti-fatigue leveling layer is 3.0 to 5.0 cm; and the thickness of the high-viscosity asphalt synchronous gravel sealing layer is 1.0 cm. According to the scheme, by increasing the structure depth of the surface of the high-toughness anti-skid ultrathin wearing layer, the service life equivalent to or even longer than that of a conventional asphalt pavement is maintained while the thickness is greatly reduced, and the problem that the overall service life of the conventional ultrathin asphalt pavement is short due to insufficient anti-skid performance is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of road engineering, and in particular to a method for constructing a lightweight and long-life asphalt pavement composite layer and a pavement structure. Background Art

[0002] Under the guidance of the "strong base and thin surface" design concept, semi-rigid base asphalt pavement has become the most important pavement structure form for high-grade roads in my country due to its advantages in integrity and bearing capacity. However, the biggest disadvantage of semi-rigid base asphalt pavement is that it is easy to crack, especially the asphalt pavement reflective cracks caused by the shrinkage and temperature shrinkage cracking of the semi-rigid material itself, which has become the most common high-grade road disease, seriously affecting the road performance and service life of the pavement.

[0003] In order to delay the extension of reflective cracks, the thickness of the asphalt surface layer will be appropriately increased during the road construction stage in China. However, due to the performance of asphalt materials and the lack of targeted anti-cracking design, the anti-reflection effect is not good and the cracking problem is still prominent. In addition, the increase in the thickness of the asphalt layer means the consumption of more asphalt and gravel resources, which increases the construction cost and also increases the environmental burden. With the continuous implementation of the country's "dual carbon" policy, the construction and maintenance requirements of road infrastructure are gradually developing in a greener and low-carbon direction. Among them, realizing the lightweight design of road structures is an important direction for the future development of green transportation.

[0004] Traditional asphalt pavement structures have technical problems such as large implementation thickness, high resource consumption and poor durability, and are prone to reflective cracking and rapid anti-skid attenuation. Summary of the invention

[0005] In view of the above-mentioned defects, the purpose of the present invention is to propose a method for constructing a lightweight and long-life asphalt pavement composite layer and a pavement structure. By improving the performance of asphalt binder, composite modification of special materials, optimization of mixture grading and improvement of pavement structure combination, the comprehensive road performance of the overall asphalt structural layer, such as fatigue resistance, low-temperature crack resistance, and high-temperature stability, is improved, and the durability and use quality of the semi-rigid base asphalt pavement structure are improved while its overall thickness is reduced, thereby achieving resource conservation and extending the service life of the pavement.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] A lightweight and long-life asphalt pavement composite layer, which includes, from top to bottom, a high-toughness anti-skid ultra-thin wear layer, an anti-rutting composite modified middle surface layer, a high-toughness porous anti-fatigue leveling layer, and a high-viscosity asphalt synchronous chip seal layer;

[0008] The thickness of the high-toughness anti-skid ultra-thin wear layer is 1.5 to 3.0 cm, and the structural depth of the surface of the high-toughness anti-skid ultra-thin wear layer is not less than 0.8 mm;

[0009] The thickness of the anti-rutting composite modified middle surface layer is 2.5 to 4.5 cm;

[0010] The thickness of the high-toughness porous anti-fatigue leveling layer is 3.0 to 5.0 cm;

[0011] The thickness of the high-viscosity asphalt synchronous chip seal layer is 1.0 cm.

[0012] Preferably, the asphalt binder used for the high-toughness anti-skid ultra-thin wear layer, the anti-rutting composite modified middle surface layer and the high-toughness porous anti-fatigue leveling layer is a first high-viscosity and high-elastic modified asphalt with a dynamic viscosity at 60°C greater than 580,000 Pa·s and a complex shear modulus at 60°C greater than 12 kPa.

[0013] Preferably, the high-toughness, anti-skid and ultra-thin wear layer is a dense-graded asphalt pavement structure, and the raw materials of the high-toughness, anti-skid and ultra-thin wear layer include 7.2 to 8.5 parts of the first high-viscosity and high-elasticity modified asphalt, 50 to 70 parts of 5 to 8 mm or 5 to 10 mm crushed stone, 15 to 25 parts of 3 to 5 mm crushed stone, 20 to 25 parts of 0 to 3 mm machine-made sand and 1 to 3 parts of mineral powder. The asphalt oil-stone ratio of the asphalt mixture formed by mixing the above raw materials is not less than 7.2%, the void ratio of the asphalt mixture is 3% to 6%, the asphalt saturation of the asphalt mixture is 75% to 85%, and the four-point bending fatigue life of the asphalt mixture is not less than 300,000 times.

[0014] Preferably, the raw material of the crushed stone in the high-toughness anti-slip ultra-thin wear layer is basalt, diabase or dense diorite.

[0015] Preferably, the anti-rutting composite modified middle surface layer is a dense-graded asphalt pavement structure, and the raw materials of the anti-rutting composite modified middle surface layer are composed of 6.3-7.5 parts of the first high-viscosity and high-elastic modified asphalt, 0-50 parts of 10-15mm crushed stone, 35-70 parts of 5-10mm crushed stone, 10-25 parts of 3-5mm crushed stone, 16-25 parts of 0-3mm machine-made sand and 1-4 parts of mineral powder, and are compounded with fiber materials and surface-activated rubber powder for composite modification. The asphalt oil-stone ratio of the asphalt mixture formed by mixing the above raw materials is not less than 6.3%, the void ratio of the asphalt mixture is 3%-6%, the asphalt saturation of the asphalt mixture is 70%-80%, the rutting dynamic stability of the asphalt mixture at 60°C is not less than 10,000 times / mm, the rutting dynamic stability of the asphalt mixture at 70°C is not less than 5,000 times / mm, and the uniaxial penetration shear strength of the asphalt mixture is not less than 1.2MPa.

[0016] Preferably, the fiber material is basalt fiber or polyester fiber, and the dosage is 0.2-0.3% of the mass of the asphalt mixture; the surface activated rubber powder is rubber powder that has been surface desulfurized using a rotary vacuum plasma treatment apparatus, has a particle size of 60-80 mesh, and is added in an amount of 2-4% of the mass of the asphalt mixture.

[0017] Preferably, the high-toughness porous anti-fatigue leveling layer is an open-graded asphalt pavement structure, and the raw materials of the high-toughness porous anti-fatigue leveling layer include 6.3-7.0 parts of the first high-viscosity and high-elasticity modified asphalt, 0-60 parts of 10-15 mm crushed stone, 20-80 parts of 5-10 mm crushed stone, 0-8 parts of 3-5 mm crushed stone, 5-20 parts of 0-3 mm machine-made sand and 1-3 parts of mineral powder. The asphalt mixture formed by mixing the above raw materials has a void ratio of more than 18%, an asphalt oil-stone ratio of the asphalt mixture of not less than 6.3%, a four-point bending fatigue life of the asphalt mixture of not less than 100,000 times, a 60°C rutting dynamic stability of the asphalt mixture of not less than 6000 times / mm, and a uniaxial penetration shear strength of the asphalt mixture of not less than 0.8 MPa.

[0018] Preferably, the raw materials of the high-viscosity asphalt synchronous chip seal layer include a second high-viscosity and high-elasticity modified asphalt and 5-10 mm chipped stone, and the second high-viscosity and high-elasticity modified asphalt is an asphalt with a dynamic viscosity at 60°C greater than 150,000 Pa·s and a complex shear modulus at 60°C greater than 10 kPa.

[0019] Preferably, the dynamic viscosity of the second high-viscosity and high-elastic modified asphalt at 60°C is not greater than 200,000 Pa·s.

[0020] A method for constructing a pavement structure, the pavement structure comprising the above-mentioned lightweight and long-life asphalt pavement composite layer, the construction method comprising the following steps:

[0021] The asphalt mixture of the high-toughness anti-skid ultra-thin wear layer, the asphalt mixture of the anti-rutting composite modified middle surface layer, the asphalt mixture of the high-toughness porous anti-fatigue leveling layer, the second high-viscosity and high-elasticity modified asphalt, cement-stabilized crushed stone mixture and graded crushed stone mixture are respectively mixed to obtain;

[0022] After the soil base is repaired, the graded crushed stone mixture is spread on the soil base and rolled to form a graded crushed stone cushion layer;

[0023] Thereafter, the cement-stabilized crushed stone mixture is spread on the graded crushed stone cushion layer and rolled to form a cement-stabilized crushed stone base layer;

[0024] Afterwards, the second high-viscosity and high-elasticity modified asphalt and 5-10mm crushed stone are successively spread on the cement-stabilized crushed stone base by a synchronous sealing vehicle, and then rolled by a rubber-wheel roller to form the high-viscosity asphalt synchronous crushed stone seal layer; the spreading amount of the second high-viscosity and high-elasticity modified asphalt is 1.8kg / m 2 ~2.5kg / m 2 , 5-10mm crushed stone spreading amount is 8-12kg / m 2 , the coverage rate is 60-70%, with non-stick wheels as the degree;

[0025] Thereafter, the asphalt mixture of the high-toughness porous anti-fatigue leveling layer is spread on the high-viscosity asphalt synchronous crushed stone seal layer, and rolled to form the high-toughness porous anti-fatigue leveling layer;

[0026] Thereafter, the asphalt mixture of the anti-rutting composite modified middle surface layer is spread on the high-toughness porous anti-fatigue leveling layer, and rolled to form the anti-rutting composite modified middle surface layer;

[0027] Thereafter, the asphalt mixture of the high-toughness anti-skid ultra-thin wear layer is spread on the anti-rutting composite modified middle surface layer, and rolled to form the high-toughness anti-skid ultra-thin wear layer.

[0028] The technical solution provided by the present invention may include the following beneficial effects:

[0029] 1. Compared with conventional asphalt pavement, this solution reduces the thickness of the composite layer by 30-60%, which can save a lot of stone and high-quality asphalt materials. While achieving a significant reduction in thickness, it maintains a service life equivalent to or even longer than that of conventional asphalt pavement, solving the problem of conventional ultra-thin asphalt pavement having a short overall service life due to insufficient anti-skid performance.

[0030] 2. Due to the reduction in implementation thickness, the production quantity of asphalt mixture is reduced, the paving and rolling process is simplified, and the implementation efficiency of each structural layer is increased by more than 100% compared with the upper, middle and lower layers of the traditional asphalt pavement structure, which can significantly shorten the construction period and reduce the impact of construction on society and traffic.

[0031] 3. When both the single-layer thickness and the total structural thickness of the pavement structure layer are thinned, the crack resistance, fatigue resistance and anti-skid durability of the pavement structure are improved, thereby achieving the goals of energy conservation, emission reduction, and economic durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the APA test of a multi-combination asphalt pavement structure in an embodiment of the present invention.

[0033] Figure 2 It is a photo of the rubbing tester in the embodiment of the present invention.

[0034] Figure 3 It is a schematic diagram of a rubbing test in an embodiment of the present invention.

[0035] Among them: high-toughness anti-skid ultra-thin wear layer 1, anti-rutting composite modified middle surface layer 2, high-toughness porous anti-fatigue leveling layer 3, high-viscosity asphalt synchronous gravel seal layer 4, precast concrete test block with cut seams 5, simulated tire load 6. DETAILED DESCRIPTION

[0036] In order to facilitate the understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0038] A lightweight and long-life asphalt pavement composite layer, which comprises, from top to bottom, a high-toughness anti-skid ultra-thin wear layer 1, an anti-rutting composite modified middle surface layer 2, a high-toughness porous anti-fatigue leveling layer 3, and a high-viscosity asphalt synchronous chip seal layer 4;

[0039] The thickness of the high-toughness anti-skid ultra-thin wear layer 1 is 1.5 to 3.0 cm, and the structural depth of the surface of the high-toughness anti-skid ultra-thin wear layer 1 is not less than 0.8 mm;

[0040] The thickness of the anti-rutting composite modified middle surface layer 2 is 2.5 to 4.5 cm;

[0041] The thickness of the high-toughness porous anti-fatigue leveling layer 3 is 3.0 to 5.0 cm;

[0042] The thickness of the high-viscosity asphalt synchronous chip seal layer 4 is 1.0 cm.

[0043] The thickness of the composite layer of conventional asphalt pavement is 18cm. This solution reduces the thickness of the composite layer of conventional asphalt pavement by 30 to 60%, which can save a large amount of stone and high-quality asphalt materials, reduce pavement weight, reduce construction energy consumption, and reduce carbon emissions, which is in line with the country's "dual carbon" strategic goals.

[0044] The service life of asphalt pavement is closely related to rutting deformation, cracking and other defects during its service life. Once serious consequences such as rutting deformation, cracking and network cracking occur, the asphalt pavement will be milled and repaved. The industry believes that this can be regarded as the terminal service life of the milled structural layer.

[0045] The construction depth of the surface of a conventional asphalt pavement is not less than 0.55mm. When the anti-skid performance of the surface layer of the asphalt pavement cannot meet the use requirements and is milled and repaved, the industry also believes that the final service life of the layer has been reached, that is, the anti-skid service life has reached the end. This solution increases the construction depth of the surface of the high-toughness anti-skid ultra-thin wear layer 1 to achieve a significant reduction in thickness while maintaining a service life equivalent to or even longer than that of a conventional asphalt pavement, solving the problem of a short overall service life of conventional ultra-thin asphalt pavements due to insufficient anti-skid performance.

[0046] At the same time, due to the reduction in implementation thickness, the production quantity of asphalt mixture is reduced, the paving and rolling process is simplified, and the implementation efficiency of each structural layer is increased by more than 100% compared with the upper, middle and lower layers of the traditional asphalt pavement structure, which can significantly shorten the construction period and reduce the impact of construction on society and traffic.

[0047] Preferably, the asphalt binder used for the high-toughness anti-skid ultra-thin wear layer 1, the anti-rutting composite modified middle surface layer 2 and the high-toughness porous anti-fatigue leveling layer 3 is a first high-viscosity and high-elastic modified asphalt with a dynamic viscosity at 60°C greater than 580,000 Pa·s and a complex shear modulus at 60°C greater than 12 kPa.

[0048] Ordinary modified asphalt materials have low viscosity and poor adhesion to aggregates. When the oil-to-stone ratio is high, the asphalt will be squeezed to the surface during construction and rolling, resulting in oil spills.

[0049] Compared with traditional modified asphalt and ordinary high-viscosity asphalt, the first high-viscosity and high-elastic modified asphalt with a dynamic viscosity of more than 580,000 Pa·s at 60℃ and a complex shear modulus of more than 12kPa at 60℃ has stronger adhesion to aggregates and can be more firmly attached to the aggregate surface, effectively improving the adhesion between aggregates and the wall hanging ability between aggregates and asphalt, so that the overall asphalt oil film thickness of the asphalt mixture is improved. The asphalt mixture formed by the first high-viscosity and high-elastic modified asphalt and aggregates can achieve a significant increase in the amount of asphalt. Under the rolling action of the roller, the problem of oil flooding on the road surface due to loose asphalt adhesion and asphalt being squeezed to the road surface will not occur. It effectively improves the toughness and fatigue cracking resistance of the asphalt mixture, and solves the problem of difficulty in increasing the oil-stone ratio.

[0050] On the other hand, when the amount of coarse aggregate is increased and the amount of fine aggregate is reduced in the optimized gradation design, the coarse aggregate will not become loose due to the lack of sufficient mortar binding and restraint made of a mixture of fine aggregate, mineral powder and asphalt, thus solving the problem of being unable to increase the amount of coarse aggregate in the optimized gradation design.

[0051] Preferably, the high-toughness, anti-skid, ultra-thin wear layer 1 is a dense-graded asphalt pavement structure, and the raw materials of the high-toughness, anti-skid, ultra-thin wear layer 1 include 7.2 to 8.5 parts of the first high-viscosity and high-elasticity modified asphalt, 50 to 70 parts of 5 to 8 mm or 5 to 10 mm crushed stone, 15 to 25 parts of 3 to 5 mm crushed stone, 20 to 25 parts of 0 to 3 mm machine-made sand and 1 to 3 parts of mineral powder. The asphalt oil-stone ratio of the asphalt mixture formed by mixing the above raw materials is not less than 7.2%, the void ratio of the asphalt mixture is 3% to 6%, the asphalt saturation of the asphalt mixture is 75% to 85%, and the four-point bending fatigue life (15°C, 1000με) of the asphalt mixture is not less than 300,000 times.

[0052] As the uppermost structural layer, the high-toughness anti-skid ultra-thin wear layer 1 will be in direct contact with the tire load, so it is necessary to have good anti-cracking, anti-deformation and anti-skid properties.

[0053] The conventional solution can only reach an asphalt-to-stone ratio of 4.6 to 5.0, because the gradation design cannot accommodate more asphalt for filling. Through gradation optimization, the above gradation design is adopted to prepare a dense-graded asphalt pavement structure with a higher proportion of coarse aggregate and a lower proportion of fine aggregate, which not only enhances the embedding stability of the aggregate skeleton, but also allows more space for filling the first high-viscosity and high-elasticity modified asphalt. By greatly increasing the amount of asphalt, the material toughness is improved, and it has a good stress dispersion effect under repeated loads, thereby improving the material toughness and crack resistance of the asphalt mixture, and improving the crack resistance and deformation resistance of the high-toughness anti-skid ultra-thin wear layer 1.

[0054] The high-toughness, anti-skid, ultra-thin wear layer 1 of the present invention adopts a skeleton-dense gradation design. Through gradation optimization, a higher proportion of coarse aggregate is used to build the mixture skeleton, reducing the amount of fine aggregate and mineral powder. On the one hand, a skeleton structure with more stable embedding ability is formed, and on the other hand, the amount of mortar formed after the fine aggregate and mineral powder are mixed with asphalt can be reduced, so that during the construction and rolling process, the amount of mortar can just fill the gaps inside the dense mixture skeleton, while preventing the mortar from being squeezed and covered on the road surface during the construction process, reducing the surface structural depth, thereby achieving a good structural depth under high asphalt dosage, so that the road surface after molding has rich structural morphology, can provide good friction and adhesion for tires, and solve the problem that the road surface structural depth is difficult to reach 0.8mm under high asphalt dosage.

[0055] In one embodiment, the raw material of the crushed stone in the high-toughness anti-slip ultra-thin wear layer 1 is limestone, shale and other non-wear-resistant stones.

[0056] Preferably, the raw material of the crushed stone in the high-toughness anti-slip ultra-thin wear layer 1 is basalt, diabase or dense diorite.

[0057] In a more preferred embodiment, hard and wear-resistant high-quality stones such as basalt, diabase or densely structured diorite are used as the crushed stone raw materials for the high-toughness anti-skid ultra-thin wear layer 1, so as to increase the anti-skid durability of the high-toughness anti-skid ultra-thin wear layer 1 and solve the problem of poor anti-skid durability of the asphalt pavement composite layer due to the use of stones with poor wear resistance.

[0058] Preferably, the anti-rutting composite modified middle surface layer 2 is a dense-graded asphalt pavement structure, and the raw materials of the anti-rutting composite modified middle surface layer 2 are composed of 6.3 to 7.5 parts of the first high-viscosity and high-elastic modified asphalt, 0 to 50 parts of 10 to 15 mm crushed stone, 35 to 70 parts of 5 to 10 mm crushed stone, 10 to 25 parts of 3 to 5 mm crushed stone, 16 to 25 parts of 0 to 3 mm machine-made sand and 1 to 4 parts of mineral powder, and are compounded with fiber materials and surface-activated rubber powder for composite modification. The asphalt oil-stone ratio of the asphalt mixture formed by mixing the above raw materials is not less than 6.3%, the void ratio of the asphalt mixture is 3% to 6%, the asphalt saturation of the asphalt mixture is 70% to 80%, the rutting dynamic stability of the asphalt mixture at 60°C is not less than 10,000 times / mm, the rutting dynamic stability of the asphalt mixture at 70°C is not less than 5,000 times / mm, and the uniaxial penetration shear strength of the asphalt mixture is not less than 1.2 MPa.

[0059] The mechanical response analysis of typical asphalt pavement structures shows that the area 3 to 7 cm away from the road surface is a high-stress area in the entire asphalt pavement structure. The shear stress is concentrated, resulting in the asphalt middle surface layer being a high-frequency layer where rutting and shear failure occur. Therefore, the anti-rutting composite modified middle surface layer 2 must have good deformation resistance and durable stability.

[0060] The main function of the middle surface layer is to resist rutting, and it has higher technical requirements for rutting dynamic stability and uniaxial penetration anti-skid strength. The asphalt mixture of the traditional middle surface layer requires a rutting dynamic stability of not less than 5000 times / mm at 60°C, a rutting dynamic stability of not less than 2500 times / mm at 70°C, and a uniaxial penetration shear strength of generally 0.6 to 0.9 MPa. The asphalt mixture of the anti-rutting composite modified middle surface layer 2 of this scheme meets higher requirements for the above-mentioned key anti-rutting indicators, so that the anti-rutting composite modified middle surface layer 2 can provide anti-rutting performance that exceeds or is equivalent to that of the traditional middle surface layer when the thickness is reduced.

[0061] At the same time, the fiber material and surface activated rubber powder are compounded for composite modification to synergistically improve the adhesion effect between the asphalt material and the aggregate, enhance the deformation restriction of the asphalt mixture under load, and form a dense-graded asphalt pavement structure with excellent resistance to high-temperature rutting and shear damage.

[0062] Preferably, the fiber material is basalt fiber or polyester fiber, and the dosage is 0.2-0.3% of the mass of the asphalt mixture; the surface activated rubber powder is rubber powder that has been surface desulfurized using a rotary vacuum plasma treatment apparatus, has a particle size of 60-80 mesh, and is added in an amount of 2-4% of the mass of the asphalt mixture.

[0063] Adding an appropriate amount of basalt fiber, polyester fiber or rubber powder that has been surface desulfurized by a rotary vacuum plasma treatment instrument to the asphalt mixture, combined with the first high-viscosity and high-elasticity modified asphalt composite modification, the high-temperature rutting resistance of the asphalt mixture is improved.

[0064] Preferably, the high-toughness porous anti-fatigue leveling layer 3 is an open-graded asphalt pavement structure, and the raw materials of the high-toughness porous anti-fatigue leveling layer 3 include 6.3 to 7.0 parts of the first high-viscosity and high-elasticity modified asphalt, 0 to 60 parts of 10 to 15 mm crushed stone, 20 to 80 parts of 5 to 10 mm crushed stone, 0 to 8 parts of 3 to 5 mm crushed stone, 5 to 20 parts of 0 to 3 mm machine-made sand and 1 to 3 parts of mineral powder. The asphalt mixture formed by mixing the above raw materials has a void ratio of more than 18%, an asphalt oil-stone ratio of the asphalt mixture of not less than 6.3%, a four-point bending fatigue life (15°C, 1000με) of the asphalt mixture of not less than 100,000 times, a 60°C rutting dynamic stability of the asphalt mixture of not less than 6000 times / mm, and a uniaxial penetration shear strength of the asphalt mixture of not less than 0.8MPa.

[0065] The lower layer is the lowest structural layer in the asphalt pavement structure. Under the action of tire load, its bottom bending tensile stress is the largest. The lower layer is connected to the cement-stabilized gravel base through a high-viscosity synchronous gravel seal layer. It also needs to directly bear the concentrated stress after cracks appear in the base. Therefore, this layer is most prone to fatigue damage and reflective cracking.

[0066] As the lower layer, the high-toughness porous anti-fatigue leveling layer 3 improves the material toughness by increasing the asphalt dosage on the one hand, and adopts a skeleton void type open grading design on the other hand, dissipates the stress at the crack tip through the void structure, inhibits the transmission of reflective cracks, thereby improving the material's ability to resist reflective cracking and fatigue cracking, and delays the extension of reflective cracks. When reflective cracks have formed inside the high-toughness porous anti-fatigue leveling layer 3, due to the presence of skeleton voids, the cracks cannot develop from bottom to top along a single path, but irregularly crack along each weak position of aggregate-asphalt adhesion to form multiple cracks, which better disperses the single concentrated stress at the crack tip and greatly delays the rate at which reflective cracks develop to the middle layer and surface layer.

[0067] Preferably, the raw materials of the high-viscosity asphalt synchronous chip seal 4 include a second high-viscosity and high-elasticity modified asphalt and 5-10 mm chipped stone, wherein the second high-viscosity and high-elasticity modified asphalt is an asphalt having a dynamic viscosity at 60°C greater than 150,000 Pa·s and a complex shear modulus at 60°C greater than 10 kPa.

[0068] Compared with traditional modified asphalt, the use of the second high-viscosity and high-elasticity modified asphalt can have a stronger effect of connecting the asphalt surface layer and the cement-stabilized gravel base layer. Moreover, due to its high shear modulus and strong elasticity, when cracks occur in the pavement base layer, the high-viscosity asphalt synchronous gravel seal layer 4 can disperse and absorb stress, delaying the reflection of cracks in the cement-stabilized gravel base layer and extending to the asphalt surface layer.

[0069] Preferably, the dynamic viscosity of the second high-viscosity and high-elastic modified asphalt at 60°C is not greater than 200,000 Pa·s.

[0070] The spraying device pressure of the synchronous chip sealer currently used in the industry is limited. If asphalt with a dynamic viscosity of more than 200,000 Pa·s at 60°C is used, there may be problems such as uneven spraying and failure to form a stable fan-shaped spray.

[0071] A method for constructing a pavement structure, the pavement structure comprising the above-mentioned lightweight and long-life asphalt pavement composite layer, the construction method comprising the following steps:

[0072] The asphalt mixture of the high-toughness anti-skid ultra-thin wear layer 1, the asphalt mixture of the anti-rutting composite modified middle surface layer 2, the asphalt mixture of the high-toughness porous anti-fatigue leveling layer 3, the second high-viscosity and high-elasticity modified asphalt, cement-stabilized crushed stone mixture and graded crushed stone mixture are respectively mixed to obtain;

[0073] After the soil base is repaired, the graded crushed stone mixture is spread on the soil base and rolled to form a graded crushed stone cushion layer;

[0074] Thereafter, the cement-stabilized crushed stone mixture is spread on the graded crushed stone cushion layer and rolled to form a cement-stabilized crushed stone base layer;

[0075] Afterwards, the second high-viscosity and high-elasticity modified asphalt and 5-10mm crushed stone are successively spread on the cement-stabilized crushed stone base by a synchronous sealing vehicle, and then rolled by a rubber-wheel roller to form the high-viscosity asphalt synchronous crushed stone seal layer 4; the spreading amount of the second high-viscosity and high-elasticity modified asphalt is 1.8kg / m 2 ~2.5kg / m 2 , 5-10mm crushed stone spreading amount is 8-12kg / m 2 , the coverage rate is 60-70%, with non-stick wheels as the degree;

[0076] Thereafter, the asphalt mixture of the high-toughness porous anti-fatigue leveling layer 3 is spread on the high-viscosity asphalt synchronous chip seal layer 4, and rolled to form the high-toughness porous anti-fatigue leveling layer 3;

[0077] Thereafter, the asphalt mixture of the anti-rutting composite modified middle surface layer 2 is spread on the high-toughness porous anti-fatigue leveling layer 3, and rolled to form the anti-rutting composite modified middle surface layer 2;

[0078] Thereafter, the asphalt mixture of the high-toughness anti-skid ultra-thin wear layer 1 is spread on the anti-rutting composite modified middle surface layer 2 and rolled to form the high-toughness anti-skid ultra-thin wear layer 1 .

[0079] In one embodiment, the pavement structure is, from top to bottom, a high-toughness anti-skid ultra-thin wear layer 1, an anti-rutting composite modified middle surface layer 2, a high-toughness porous anti-fatigue leveling layer 3, a high-viscosity asphalt synchronous crushed stone seal layer 4, a cement-stabilized crushed stone base layer, a graded crushed stone cushion layer and a soil base. Among them, the graded crushed stone cushion layer is a structural layer formed by rolling crushed stones and fillers of different specifications and reasonable grading, and the cement-stabilized crushed stone is a structural layer formed by paving, rolling and curing with a certain amount of cement cementitious materials filling the gaps of aggregates with graded crushed stones as the skeleton. The graded crushed stone cushion layer and the cement-stabilized crushed stone base layer are both granular cushion layers and semi-rigid base structure systems commonly used in traditional asphalt pavements, and there are no special requirements.

[0080] By adopting the above-mentioned pavement structure construction method, the crack resistance, fatigue resistance and anti-skid durability of the pavement structure can be improved while reducing the single-layer thickness and the total structure thickness of the pavement structure layer, thereby achieving the goals of energy conservation, emission reduction, economy and durability.

[0081] Example 1

[0082] A lightweight and long-life pavement structure, the composition of which is as follows:

[0083] The first high-viscosity and high-elasticity modified asphalt uses a modified asphalt with a dynamic viscosity of >580,000 Pa·s at 60°C and a complex shear modulus of 15.2 kPa at 60°C. The second high-viscosity and high-elasticity modified asphalt uses a high-viscosity and high-elasticity modified asphalt with a dynamic viscosity of 186,000 Pa·s at 60°C and a complex shear modulus of 10.5 kPa at 60°C.

[0084] The parameters of the asphalt mixture in the high-toughness anti-skid ultra-thin wear layer 1 are: oil-stone ratio is 7.5%, void ratio is 4.5%, asphalt saturation is 80.5%, surface structure depth is 1.05mm, and four-point bending fatigue life (15°C, 1000με) is 486550 times.

[0085] The parameters of the asphalt mixture in the anti-rutting composite modified middle surface layer 2 are: oil-stone ratio is 6.6%, void ratio is 4.2%, asphalt saturation is 76.4%, rutting dynamic stability at 60℃ is 12550 times / mm, rutting dynamic stability at 70℃ is 7540 times / mm, and uniaxial penetration shear strength is 1.5Mpa.

[0086] The parameters of the asphalt mixture in the high-toughness porous anti-fatigue leveling layer 3 are: oil-stone ratio is 6.3%, the void ratio is 20.3%, the four-point bending fatigue life (15℃, 1000με) is 155680 times, the rutting dynamic stability at 60℃ is 7626 times / mm, and the uniaxial penetration shear strength is 1.05MPa.

[0087] The pavement structure from top to bottom is as follows:

[0088] High toughness anti-skid ultra-thin wear layer 1, the thickness of which is 2.0 cm;

[0089] The anti-rutting composite modified middle surface layer 2 has a thickness of 3.0 cm;

[0090] High-toughness porous anti-fatigue leveling layer 3, with a thickness of 4.0 cm;

[0091] High viscosity asphalt synchronous chip seal 4, the thickness of which is 1.0 cm;

[0092] Cement stabilized gravel base with a thickness of 36cm;

[0093] Graded crushed stone cushion layer, with a thickness of 18cm;

[0094] Soil foundation.

[0095] Example 2

[0096] A lightweight and long-life pavement structure, wherein the asphalt mixture parameters of the high-toughness anti-skid ultra-thin wear layer 1, the anti-rutting composite modified middle surface layer 2, the high-toughness porous anti-fatigue leveling layer 3 and the high-viscosity asphalt synchronous chip seal layer 4 are the same as those in Example 1, and the pavement structure is as follows from top to bottom:

[0097] High toughness anti-skid ultra-thin wear layer 1, the thickness of which is 1.5 cm;

[0098] The anti-rutting composite modified middle surface layer 2 has a thickness of 3.5 cm;

[0099] High-toughness porous anti-fatigue leveling layer 3, with a thickness of 4.0 cm;

[0100] High viscosity asphalt synchronous chip seal 4, the thickness of which is 1.0 cm;

[0101] Cement stabilized gravel base, with a thickness of 36.0 cm;

[0102] Graded crushed stone cushion layer, with a thickness of 18.0 cm;

[0103] Soil foundation.

[0104] Example 3

[0105] A lightweight and long-life pavement structure, wherein the asphalt mixture parameters of the high-toughness anti-skid ultra-thin wear layer 1, the anti-rutting composite modified middle surface layer 2, the high-toughness porous anti-fatigue leveling layer 3 and the high-viscosity asphalt synchronous chip seal layer 4 are the same as those in Example 1, and the pavement structure is as follows from top to bottom:

[0106] High toughness anti-skid ultra-thin wear layer 1, the thickness of which is 2.0 cm;

[0107] The anti-rutting composite modified middle surface layer 2 has a thickness of 4.0 cm;

[0108] High-toughness porous anti-fatigue leveling layer 3, with a thickness of 3.0 cm;

[0109] High viscosity asphalt synchronous chip seal 4, the thickness of which is 1.0 cm;

[0110] Cement stabilized gravel base, with a thickness of 36.0 cm;

[0111] Graded crushed stone cushion layer, with a thickness of 18.0 cm;

[0112] Soil foundation.

[0113] Comparative Example 1

[0114] The traditional asphalt pavement structure, the pavement structure from top to bottom is:

[0115] AC-13 asphalt top layer, with a thickness of 4.0 cm;

[0116] AC-20 asphalt middle surface layer, with a thickness of 6.0 cm;

[0117] AC-25 asphalt bottom layer, with a thickness of 8.0 cm;

[0118] Modified asphalt synchronous chip seal, the thickness of which is 1.0 cm;

[0119] Cement stabilized gravel base, with a thickness of 36.0 cm;

[0120] Graded crushed stone cushion layer, with a thickness of 18.0 cm;

[0121] Soil foundation.

[0122] Among them, the asphalt mixture in the AC-13 asphalt upper layer and the AC-20 asphalt middle layer both use ordinary modified asphalt, and the parameters of the modified asphalt are: 60℃ dynamic viscosity is 5000~10000Pa·s, 60℃ complex shear modulus is 2~3kPa; the asphalt mixture in the AC-25 asphalt lower layer uses 70# matrix asphalt, and the parameters of 70# matrix asphalt are: 60℃ dynamic viscosity is 200~350Pa·s, 60℃ complex shear modulus is 1~1.5kPa.

[0123] The parameters of the asphalt mixture in the AC-13 asphalt upper layer are: oil-stone ratio of 5.0%, void ratio of 4.2%, asphalt saturation of 70.2%, and surface texture depth of 0.65mm; the parameters of the asphalt mixture in the AC-20 asphalt middle layer are: oil-stone ratio of 4.5%, void ratio of 4.7%, and asphalt saturation of 68.5%; the parameters of the asphalt mixture in the AC-25 asphalt lower layer are: oil-stone ratio of 4.1%, void ratio of 4.0%, asphalt saturation of 69.3%, and there is no requirement for four-point bending fatigue life.

[0124] Test method:

[0125] A multi-combination asphalt pavement test specimen with 5 prefabricated concrete test blocks with cutouts was formed indoors, and the crack resistance and deformation resistance tests were conducted using an asphalt pavement automatic analyzer (APA test machine). Figure 1 As shown, the test method can quickly, intuitively and realistically simulate the process of reflective cracking and rutting deformation of the entire asphalt pavement structure when cracks appear in the base layer by laying a multi-combination asphalt pavement structure on a precast concrete test block 5 with a slit and applying a reciprocating simulated tire load 6 to the entire test piece.

[0126] APA test (wheel pressure of 123kg) was carried out on the molded array of multi-combination APA test specimens. The number of tire actions when reflective cracks appeared on the surface of each group of specimens was recorded as the anti-reflective cracking life. The rutting thickness of the specimens when running 50,000 times, 100,000 times, 150,000 times and 200,000 times was also recorded to evaluate the anti-cracking and anti-deformation properties of different types of multi-combination asphalt pavement structures.

[0127] Table 1- Comparison of anti-cracking and anti-deformation performance of different types of multi-combination asphalt pavement structures

[0128]

[0129] It can be found from Table 1 that the lightweight and long-life pavement structure proposed in the present invention has obvious advantages in anti-cracking performance and anti-deformation performance compared with the traditional modified asphalt pavement structure combination.

[0130] An indoor rubbing test was conducted on rubbing slab specimens made of an asphalt mixture of a high-toughness, anti-skid ultra-thin wear layer 1 and an AC-13 asphalt top layer, and the structure depth test was used to verify the change in surface structure depth of the rubbing slab specimens after 0, 2, 4, 6, and 8 hours of rubbing, so as to compare and analyze the difference in anti-skid durability between the two.

[0131] like Figure 2 and Figure 3 As shown in the figure, the rubbing test is carried out in a 60℃ water bath environment, using a tire in a rubbing test machine to carry out a "W"-shaped motion in both the vertical and horizontal directions on the surface of the rubbing plate specimens with high toughness anti-skid ultra-thin wear layer 1 and AC-13 asphalt upper layer, so as to realize the rubbing and grinding of the tire on the entire surface of the rubbing plate specimen, and truly simulate the reciprocating motion and wear effect of the tire on the asphalt pavement. Before the rubbing test (i.e., 0h), the structural depth of the rubbing plate specimens with high toughness anti-skid ultra-thin wear layer 1 and AC-13 asphalt upper layer was measured, and then the rubbing plate specimens were put into the test machine for testing. The rubbing plate specimens were taken out every 2 hours of rubbing, and the surface structural depths of the rubbing plate specimens after rubbing for 2h, 4h, 6h and 8h were measured after natural air drying. The summary statistics are shown in Table 2.

[0132] Table 2 Summary of surface structure depth changes of high-toughness anti-skid ultra-thin wear layer and AC-13 asphalt top layer at different rubbing stages

[0133]

[0134] It can be found from Table 2 that, as the surface layer in contact with the tire, the high-toughness anti-skid ultra-thin wear layer 1 is superior to the traditional AC-13 asphalt top layer in terms of both initial anti-skid performance and overall anti-skid durability.

[0135] Combining Table 1 and Table 2, it can be seen that the application of the present invention can reduce the thickness of the asphalt pavement composite layer by about 50%, while improving the pavement's anti-cracking performance, anti-deformation performance and anti-skid performance, thereby extending the overall service life of the pavement structure.

[0136] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0137] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A lightweight and long-life asphalt pavement composite layer, characterized by: From top to bottom, they are high-toughness anti-skid ultra-thin wear layer, anti-rutting composite modified middle surface layer, high-toughness porous anti-fatigue leveling layer and high-viscosity asphalt synchronous chip seal layer; The thickness of the high-toughness anti-skid ultra-thin wear layer is 1.5 to 3.0 cm, and the structural depth of the surface of the high-toughness anti-skid ultra-thin wear layer is not less than 0.8 mm; The thickness of the anti-rutting composite modified middle surface layer is 2.5 to 4.5 cm; The thickness of the high-toughness porous anti-fatigue leveling layer is 3.0 to 5.0 cm; The thickness of the high-viscosity asphalt synchronous chip seal layer is 1.0 cm.

2. The lightweight and long-life asphalt pavement composite layer according to claim 1 is characterized by: The asphalt binder used for the high-toughness anti-skid ultra-thin wear layer, the anti-rutting composite modified middle surface layer and the high-toughness porous anti-fatigue leveling layer is the first high-viscosity and high-elastic modified asphalt with a dynamic viscosity of more than 580,000 Pa·s at 60°C and a complex shear modulus of more than 12 kPa at 60°C.

3. The lightweight and long-life asphalt pavement composite layer according to claim 2 is characterized by: The high-toughness, anti-skid and ultra-thin wear layer is a dense-graded asphalt pavement structure. The raw materials of the high-toughness, anti-skid and ultra-thin wear layer include 7.2 to 8.5 parts of the first high-viscosity and high-elasticity modified asphalt, 50 to 70 parts of 5 to 8 mm or 5 to 10 mm crushed stone, 15 to 25 parts of 3 to 5 mm crushed stone, 20 to 25 parts of 0 to 3 mm machine-made sand and 1 to 3 parts of mineral powder. The asphalt oil-stone ratio of the asphalt mixture formed by mixing the above raw materials is not less than 7.2%, the void ratio of the asphalt mixture is 3% to 6%, the asphalt saturation of the asphalt mixture is 75% to 85%, and the four-point bending fatigue life of the asphalt mixture is not less than 300,000 times.

4. The lightweight and long-life asphalt pavement composite layer according to claim 3 is characterized by: The raw material of the crushed stone in the high-toughness anti-slip ultra-thin wear layer is basalt, diabase or diorite with a dense structure.

5. The lightweight and long-life asphalt pavement composite layer according to claim 2 is characterized by: The anti-rutting composite modified middle surface layer is a dense-graded asphalt pavement structure. The raw materials of the anti-rutting composite modified middle surface layer are composed of 6.3 to 7.5 parts of the first high-viscosity and high-elasticity modified asphalt, 0 to 50 parts of 10 to 15 mm crushed stone, 35 to 70 parts of 5 to 10 mm crushed stone, 10 to 25 parts of 3 to 5 mm crushed stone, 16 to 25 parts of 0 to 3 mm machine-made sand and 1 to 4 parts of mineral powder, and are compounded with fiber materials and surface-activated rubber powder for composite modification. The asphalt oil-stone ratio of the asphalt mixture formed by mixing the above raw materials is not less than 6.3%, the void ratio of the asphalt mixture is 3% to 6%, the asphalt saturation of the asphalt mixture is 70% to 80%, the rutting dynamic stability of the asphalt mixture at 60°C is not less than 10,000 times / mm, the rutting dynamic stability of the asphalt mixture at 70°C is not less than 5,000 times / mm, and the uniaxial penetration shear strength of the asphalt mixture is not less than 1.2 MPa.

6. The lightweight and long-life asphalt pavement composite layer according to claim 5 is characterized by: The fiber material is basalt fiber or polyester fiber, and the amount thereof is 0.2-0.3% of the mass of the asphalt mixture; the surface activated rubber powder is rubber powder that has been surface desulfurized by a rotary vacuum plasma treatment apparatus, and has a particle size of 60-80 meshes, and the amount thereof is 2-4% of the mass of the asphalt mixture.

7. The lightweight and long-life asphalt pavement composite layer according to claim 2 is characterized by: The high-toughness porous anti-fatigue leveling layer is an open-graded asphalt pavement structure. The raw materials of the high-toughness porous anti-fatigue leveling layer include 6.3 to 7.0 parts of the first high-viscosity and high-elasticity modified asphalt, 0 to 60 parts of 10 to 15 mm crushed stone, 20 to 80 parts of 5 to 10 mm crushed stone, 0 to 8 parts of 3 to 5 mm crushed stone, 5 to 20 parts of 0 to 3 mm machine-made sand and 1 to 3 parts of mineral powder. The asphalt mixture formed by mixing the above raw materials has a void ratio of more than 18%, an asphalt oil-stone ratio of the asphalt mixture of not less than 6.3%, a four-point bending fatigue life of the asphalt mixture of not less than 100,000 times, a 60°C rutting dynamic stability of the asphalt mixture of not less than 6000 times / mm, and a uniaxial penetration shear strength of the asphalt mixture of not less than 0.8 MPa.

8. The lightweight and long-life asphalt pavement composite layer according to claim 1 is characterized by: The raw materials of the high-viscosity asphalt synchronous chip seal layer include a second high-viscosity and high-elasticity modified asphalt and 5-10 mm chipped stone. The second high-viscosity and high-elasticity modified asphalt is an asphalt with a dynamic viscosity of more than 150,000 Pa·s at 60°C and a complex shear modulus of more than 10 kPa at 60°C.

9. The lightweight and long-life asphalt pavement composite layer according to claim 8, characterized in that: The dynamic viscosity of the second high-viscosity and high-elastic modified asphalt at 60°C is not greater than 200,000 Pa·s.

10. A method for constructing a pavement structure, characterized in that: The pavement structure comprises the lightweight and long-life asphalt pavement composite layer according to any one of claims 1 to 9, and the construction method comprises the following steps: The asphalt mixture of the high-toughness anti-skid ultra-thin wear layer, the asphalt mixture of the anti-rutting composite modified middle surface layer, the asphalt mixture of the high-toughness porous anti-fatigue leveling layer, the second high-viscosity and high-elasticity modified asphalt, cement-stabilized crushed stone mixture and graded crushed stone mixture are respectively mixed to obtain; After the soil base is repaired, the graded crushed stone mixture is spread on the soil base and rolled to form a graded crushed stone cushion layer; Thereafter, the cement-stabilized crushed stone mixture is spread on the graded crushed stone cushion layer and rolled to form a cement-stabilized crushed stone base layer; Afterwards, the second high-viscosity and high-elasticity modified asphalt and 5-10mm crushed stone are successively spread on the cement-stabilized crushed stone base by a synchronous sealing vehicle, and then rolled by a rubber-wheel roller to form the high-viscosity asphalt synchronous crushed stone seal layer; the spreading amount of the second high-viscosity and high-elasticity modified asphalt is 1.8kg / m 2 ~2.5kg / m 2 , 5-10mm crushed stone spreading amount is 8-12kg / m 2 , the coverage rate is 60-70%, with non-stick wheels as the degree; Thereafter, the asphalt mixture of the high-toughness porous anti-fatigue leveling layer is spread on the high-viscosity asphalt synchronous crushed stone seal layer, and rolled to form the high-toughness porous anti-fatigue leveling layer; Thereafter, the asphalt mixture of the anti-rutting composite modified middle surface layer is spread on the high-toughness porous anti-fatigue leveling layer, and rolled to form the anti-rutting composite modified middle surface layer; Thereafter, the asphalt mixture of the high-toughness anti-skid ultra-thin wear layer is spread on the anti-rutting composite modified middle surface layer, and rolled to form the high-toughness anti-skid ultra-thin wear layer.

Citation Information

Cited By

  • Anti-rutting-anti-displacement layered composite asphalt material for level crossing road and gradient construction method thereof

    CN121023893A